Effect of Aqueous Extract of Cyperus rotundus on Hyperlipidaemia in Rat Model - Chandratre, R S (International Journal of Pharmaceutical & Biological Archive, 2012)
Effect of Aqueous Extract of Cyperus rotundus on Hyperlipidaemia in Rat Model